Cultural authority in the age of Whitman a transatlantic perspective - Leypoldt, Günter (Edinburgh University Press, 2009)
This book deals with narratives of cultural legitimation in nineteenth-century US literature in a transatlantic context
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Whitman, Walt / 1819-1892 / Criticism and interpretation; Whitman, Walt -- 1819-1892; Kulturelle Identität; USA